Scenario Model to Mitigate Traffic Congestion and Improve Commuting Time Efficiency - Shabrina Luthfiani Khanza; Erma Suryani; Rully Agus Hendrawan (Journal of Information Systems Engineering and Business Intelligence, 2021)
Background: Commuting time is highly influenced by traffic congestion. System dynamics simulation can help identify the cause of traffic problems to improve travel time efficiency.Objective: This study aims to reduce traffic congestion and minimise commuting time efficiency using system dynamics simulation and scenarios. The developed scenarios implement the Bus Rapid Transit (BRT) and trams projects in the model.Methods: System dynamics simulation is used to analyse the transport system in Surabaya and the impact of BRT and trams project implementation in the model in order to improve commuting time and to reduce congestion.Results: From the simulation results, with the implementation of BRT and tram projects along with highway expansion, traffic congestion is predicted to decline by 24-44%.  With the reduction of traffic congestion, travel time efficiency is predicted to improve by 11-28%. On the contrary, implementation of BRT and tram project without highway expansion is predicted to increase the traffic congestion by 5% in the initial year of implementation, then traffic congestion is predicted to decline by 2% in 2035.Conclusion: Based on the scenarios, transport project implementation such as BRT and trams should be accompanied with improvement of infrastructure. Further research is needed to develop a more comprehensive transportation system to capture a broader view of the problem. Keywords: Model, Simulation, System Dynamics, Traffic Congestion, Travel Time